Essential oils for dairy calves: effects on performance, scours, rumen fermentation and intestinal fauna - F.H.R. Santos; M.R. De Paula; D. Lezier; J.T. Silva; G. Santos; C.M.M. Bittar (Animal, 2015)
The first cause of death of dairy calves is often diarrhea which is mainly caused by pathogenic bacteria, which can result in excessive use of antibiotics. However, facing the increase concern by the industry and consumers, the use of antibiotics not only to control pathogens, but also to manipulate growth, has become a challenge. Alternative additives, such essential oils, have the potential to decrease antibiotic use, without reducing performance or increasing mortality of dairy calves. The objective of this study was to evaluate the use of a commercial blend of essential oils, incorporated into the calf starter and/or milk replacer to monitor the effect on overall calf performance, fecal scores and rumen fermentation parameters. A total of 30 Holstein calves received 6 l/day of a liquid diet, consisting of a commercial milk replacer containing 20% CP : 15% fat (EE). Calves had free choice access to water and calf starter. Weaning occurred at week 8, and calves were followed until the 10th week of age. Calves were assigned to one of the three treatment groups in a randomized block design. Treatments: (1) control without essential oils supplementation (C); (2) essential oils blend in the milk replacer at 400 mg/kg (MR) and (3) essential oils blend in the milk replacer (200 mg/kg) and starter feed (200 mg/kg) (MRS). From the 2nd week, calves were weighed and body measurements were taken, while concentrate intake and fecal scores were monitored daily. Blood samples were drawn weekly for determination of glucose and β-hydroxybutyrate. Fecal samples were collected weekly and analyzed for lactic acid bacteria and Enterobacteria; and ruminal fluid for determination of pH, short chain fatty acids, ammonia-N and counts of amylolytic and cellulolytic bacteria, and protozoa. Performance, fecal scores and intestines microorganisms were not affected by the essential oils supplementation. Ruminal and blood parameters were also not affected, with the exception the rumen ammonia-N concentration, with higher values when essential oils were supplemented in a combination of milk replacer and starter feed. Most of the evaluated parameters were affected by age of calves, mainly as a response to the increase in concentrate intake as animals’ aged. Essential oils are promising substitutes for antibiotics. However, the dose and routes of administration deserve further studies, allowing a better animal performance and health to be achieved.